Development of a preliminary habitat assessment and planning tool for mountain caribou in southeast British Columbia - Apps, Clayton D.; Kinley, Trevor A. (Rangifer, 1998)
The Purcell Mountains of southeast British Columbia support a population of mountain caribou near the southernmost extension of their range. This ecotype is dependent upon late-successional forests, largely because such stands provide arboreal lichen for winter forage. Recent provincial forest practices legislation and land-use planning initiatives have provided the impetus for developing an interim caribou habitat assessment model for use as a planning tool. We applied an HSI (habitat suitability index) model developed for a nearby population as a testable hypothesis of caribou habitat selection in the southern Purcells. In a study area of about 6000 km2, 512 radiolocations were obtained for 22 animals from 1993 through 1995. Seasonal selectivity was assessed for the following model variables: elevation, slope, habitat type/current cover type, overstory size class, canopy closure, and age of dominant overstory. Caribou were most selective for stand age, which the model also defined as the greatest determinant of habitat suitability. However, we did not judge overall model output to be an adequate predictor of habitat selection by southern Purcell caribou. Seasonal ratings for each variable were therefore modified to better reflect selection patterns by animals in this study, and subjectively adjusted to ensure that potentially limiting habitat types were rated highly. An evaluation of the adjusted model established its efficacy as an interim decision-support tool. Selection analyses of spatial habitat distribution levels indicated a preference by caribou for landscapes with at least 40% suitable habitat per 250 ha and per 5000 ha. From this, it is apparent that suitable habitat is highly fragmented in this study area.